William Lloyd Garrison and Giuseppe Mazzini : Abolition, Democracy, and Radical Reform - Dal Lago, Enrico (Book collections on Project MUSE., 2013)
William Lloyd Garrison and Giuseppe Mazzini, two of the foremost radicals of the nineteenth century, lived during a time of profound economic, social, and political transformation in America and Europe. Both born in 1805, but into dissimilar family backgrounds, the American Garrison and Italian Mazzini led entirely different lives -- one as a citizen of a democratic republic, the other as an exile proscribed by most European monarchies. Using a comparative analysis, Enrico Dal Lago suggests that Garrison and Mazzini nonetheless represent a connection between the egalitarian ideologies of Am.